If you love a mermaid tale / The little mermaid and the magic shell - Pirotta, Saviour (Hauppauge : Barron's Educational Series, 2010)
Two captivating mermaid tales feature artist Susanna Lockheart's beautifully atmospheric and highly detailed color illustrations.
H
b
b